2012
DOI: 10.9790/3013-25205155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microalbuminuria among sudanese type 2 diabetic patients at elmusbah center at ombadda - omdurman

Abstract: Abstract--Microalbuminuria is persistent albumin excretion between 30 and 300 mg/day, in patients with diabetes it is usually indicative of diabetic nephropathy which is most common cause of end stage renal disease, it is also associated with cardiovascular disease. Early detection of microalbuminuria and early control of diabetes retards the development of structural changes in early diabetic nephropathy. The main objective was to determine the prevalence of microalbuminuria on urine samples of Sudanese type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…The rise in the prevalence of diabetic nephropathy in our study might be a result of apparent deficiency in the primary health care during the last five years in Yemen because of the war and political conflicts. Although the prevalence of microalbuminuria was unexpectedly high, this is consistent with studies in Saudi Arabia (45.6%) [28], in Sudan 44% [29] and in Kuwait 58.2% [30].…”
Section: Discussionsupporting
confidence: 89%
“…The rise in the prevalence of diabetic nephropathy in our study might be a result of apparent deficiency in the primary health care during the last five years in Yemen because of the war and political conflicts. Although the prevalence of microalbuminuria was unexpectedly high, this is consistent with studies in Saudi Arabia (45.6%) [28], in Sudan 44% [29] and in Kuwait 58.2% [30].…”
Section: Discussionsupporting
confidence: 89%
“…Our diabetic population was characterized by a female majority, as described in the literature [ 18 , 19 ]. Different distributions were found though [ 20 , 21 ]. The mean age (61.4 years) and the mean duration of diabetes (8.1 years (SD: 6.4)) were similar to those reported by other authors [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using Bland-Altman method of comparative analysis which 3). diabetes subjects [29]. Abundant research has shown that diabetes and its complications play a significant role in the dysfunction of the glomerular basement membrane (GBM) filtration barrier; thus, albumin can be secreted into urine [30][31][32].…”
Section: Data Are Presented As Absolute Values: Cg -Cockcroft-gault 4...mentioning
confidence: 99%